1999
DOI: 10.3168/jds.s0022-0302(99)75468-8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Milk Yield of Holstein Cows in Mexico and the United States

Abstract: Genotype by environment interaction for milk yield was investigated by analyzing 55,162 mature equivalent, first lactation records of daughters from 1339 Holstein sires in Mexico and 499,401 daughters from 663 Holstein sires in the northeastern US. There were 474 US sires in common. Herd-year standard deviation was used to define non-overlapping high (> or = 1600 kg) and low (< or = 1300 kg) Mexican environments and a low (< or = 1025 kg) US environment. Variance components across Mexican environments were abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
45
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 16 publications
12
45
2
1
Order By: Relevance
“…The additive genetic variance from confinement was 4.1 times higher than that from grazing and the residual variance was only 2.3 times higher. This agrees with the reported phenotypic means from confinement and grazing of our study (Table 1) and with studies that have shown less genetic variation in lower production herds (Cromie et al, 1998;Cienfuegos-Rivas et al, 1999;Kearney et al, 2004). Boettcher et al (2003) estimated higher heritability using herds in confinement than in grazing, and suggested that genetic differences among animals were better expressed in herds under confinement.…”
Section: Genetic Correlationsupporting
confidence: 93%
“…The additive genetic variance from confinement was 4.1 times higher than that from grazing and the residual variance was only 2.3 times higher. This agrees with the reported phenotypic means from confinement and grazing of our study (Table 1) and with studies that have shown less genetic variation in lower production herds (Cromie et al, 1998;Cienfuegos-Rivas et al, 1999;Kearney et al, 2004). Boettcher et al (2003) estimated higher heritability using herds in confinement than in grazing, and suggested that genetic differences among animals were better expressed in herds under confinement.…”
Section: Genetic Correlationsupporting
confidence: 93%
“…In sheep breeding, providing there are suitable levels of genetic linkage between flocks, BLUP allows estimated breeding values (EBVs) to be expressed relative to a common base, from which direct comparisons can be made across flocks. However, a problem that farmers can encounter is that having selected to use an individual animal based on their predicted performance, they obtain somewhat unexpected and inconsistent results when they are used in another location (Cienfuegos-Rivas et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of highly productive breeds of dairy cattle into an extensive environment will often lead to reduced milk production, as well as an increased risk of reproductive and metabolic disorders (Calus & Veerkamp, 2003;Cienfugos-Rivas et al, 1999;Horan et al, 2005). Thus, breeds well adapted to the environmental conditions in Western Europe may be poorly suited to the more extensive Kosovo environment.…”
Section: Characteristics Of Analysed Traitsmentioning
confidence: 99%